ANALISIS PARETO SEDIAAN SOLID FLU DAN BATUK DI SALAH SATU APOTEK DI KUNINGAN - Erfiansyah Erfiansyah; Herliningsih Herliningsih (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2018)
Flu and cough illness is a disease that is often experienced by everyone. Drug flu and cough planning or control is urgently needed so that the management of each drug is easier. Pareto analysis or 80/20 pareto law is one of the methods used in logistics management to divede groups of goods into three namely A, B, and C. This research is aimed at identifying cold medicine and solid cough according to usage value and investment value so that effective managemen can concentrate ond cold medicine and solid cough preparation which is small but has big investment value. This research is a non-experimental study through a propective study by observing drug sales for 2 months. The subjects of this study are flu drug sales and solid cough sales data from January 2017 – February 2017. From the result of this study found that flu drugs and solid cough preparations that enter into group A amounted to 7 items, while the entry into group B amounted to 8 items, and that included into group C there are are 14 items.